Logistični polinomi - Razpet, Marko (Obzornik za matematiko in fiziko, 2011)
It is shown how the normalized logistic function generates a sequence of polynomials. Some properties of these polynomials are discussed and some relations with Bernoulli and Stirling numbers are given.
Keywords: Bernoullijeva števila; logistična funkcija; logistični polinomi; matematika; mathematics; nelinearna rekurzija; Stirlingova števila